What Makes Individuals Stick to Their Exercise Regime? A One-Year Follow-Up Study Among Novice Exercisers in a Fitness Club Setting - Gjestvang, Christina; Abrahamsen, Frank; Stensrud, Trine; Haakstad, Lene A. H. (Frontiers in Psychology, 2021)
Objectives: A fitness club may be an important arena to promote regular exercise. However, authors have reported low attendance rates (10% to 37%) the first months after individuals sign up for membership. It is therefore important to understand the reasons for poor exercise adherence. In this project, we aimed to investigate different psychosocial factors that might increase the likelihood of reporting regular exercise the first year of a fitness club membership, including self-efficacy, motives, social support, life satisfaction, and customer satisfaction. Methods: New members (≤four weeks membership, n = 250) classified as novice exercisers (exercise <60 min/week the last six months) from 25 multipurpose gyms were followed for one year. Data were collected by an electronic survey including background and health factors, self-efficacy, social support, life satisfaction, motives, customer satisfaction, and exercise attendance, and was answered at start-up and after three (n = 224), six (n = 213), and 12 (n = 187) months. It is well established in the literature that ≥2 exercise sessions/week improve physical fitness in novice exercisers (if adhered to). Hence, we divided the participants into regular exercise attendance (≥2 sessions/week) and non-regular exercise attendance (≤1 session/week, exercise dropout, or membership dropout) in the analysis. Results: A mixed-effects logistic regression model revealed that the strongest predictor for reporting regular exercise attendance was higher levels of the motive “enjoyment” (OR = 1.84, p = <0.001, 95% CI for OR = 1.35, 2.50), followed by self-efficacy “sticking to it” (OR = 1.73, p = 0.002, 95% CI for OR = 1.22, 2.46) and social support from friends and family (OR = 1.16, p = <0.001, 95% CI for OR = 1.09, 1.23). Conclusion: In novice exercisers, regular exercise at three, six, and 12 months was associated with higher scores of the motive “enjoyment”, self-efficacy (“sticking to it”), and social support compared with non-regular exercise. Our results show that the majority of new fitness club members do not achieve regular exercise behavior.